2024
DOI: 10.1109/tem.2023.3293855
|View full text |Cite
|
Sign up to set email alerts
|

Conflict Management Strategies and the Digitalization of Family Firms: The Moderating Role of Generational Ownership Dispersion

Abstract: Family business research indicates that digital transformation may lead to substantial conflicts. However, little is known about how conflict management strategies address such conflicts. We thus mobilize conflict theory and empirically examine the impact of these strategies on the level of family business digitalization and whether such strategies are contingent on the number of ownership generations involved. To do so, we draw on a combination of a survey of 85 German family firms and in-depth interviews wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 163 publications
0
1
0
Order By: Relevance
“…Extant literature indicates that problem-solving behaviors, which are a combination of integrating and compromising styles, have a mitigating effect on job stress. Teams that adopt problemsolving strategies tend to have better communication, greater satisfaction, and lower stress levels (Bürgel & Hiebl, 2023). A study by Friedman et al (2000) found that problem-solving approaches are inversely related to levels of job stress, supporting the notion that cooperative behaviors can alleviate tension in the workplace.…”
Section: Problem-solving Behavior and Work Stressmentioning
confidence: 93%
“…Extant literature indicates that problem-solving behaviors, which are a combination of integrating and compromising styles, have a mitigating effect on job stress. Teams that adopt problemsolving strategies tend to have better communication, greater satisfaction, and lower stress levels (Bürgel & Hiebl, 2023). A study by Friedman et al (2000) found that problem-solving approaches are inversely related to levels of job stress, supporting the notion that cooperative behaviors can alleviate tension in the workplace.…”
Section: Problem-solving Behavior and Work Stressmentioning
confidence: 93%